STRATEGY FOR THE DEVELOPMENT OF CHONBURI PROVINCIAL ADMINISTRATIVE ORGANIZATION TO SUPPORT EASTERN SPECIAL DEVELOPMENT ZONE - Klindee, Manusak; Thampitug, Supranee (Journal of Educational Review Faculty of Education in MCU, 2020)
The purpose of this research article : 1) to establish the strategy for the development of Chonburi Provincial Administrative Organization and 2) to make a suggestion for the development of Chonburi Provincial Administrative Organization to support Eastern Special Development Zone, used qualitative research as a guideline in finding research answers, including documentary research, in-depth interviews and brain storming, the key informants used in this study consist of 4 groups which were Group 1: Group of Eastern Special Development Zone policy-makers, the amount of 5 people, Group 2: Group of executives in Chonburi Provincial Administrative Organization were the top executives of the department, consist of 10 executives of the department or representatives, Group 3: Personnel in Chonburi Provincial Administrative Organization consist of government officials and employees, an amount of 30 people, and Group 4: Group of people using the service of Chonburi Provincial Administrative Organization, an amount of 52 people, data analysis used content analysis in contextual unit, including analytic induction and comparative analysis by comparing the similarities and differences that exist in the qualities and attributes of the data. The results of the research found that: 1) the strategy for the development of Chonburi Provincial Administrative Organization to support Eastern Special Development Zone consisting of 5 strategies, which were Strategy 1 Promote digital and innovation organization, Strategy 2 Develop quality spatial information centers, Strategy 3 Create the image of the organization, Strategy 4 Develop human resource management system, and Strategy 5 Improve rules and regulations to be modern in accordance with the situation, which all 5 strategies have relation and are linked together in a systematic way and in accordance with the goals of national policies and plans and 2) there will be findings in the proposal to have a new division in Chonburi Provincial Administrative Organization, the structure of the new division should have 4 main functions such as Subdivision of Spatial Database, Subdivision of Knowledge Management, Subdivision of Coordination and Subdivision of Plan Integration, focusing on creating a small, streamlined organization and a modern organization by using digital technology.